Leverage, capital and profitability of the banks: Evidence from Saudi Arabia - Shaik, Abdul Rahman (Accounting, 2021)
The study examines the effect of leverage and capital on the profitability of selected Saudi Arabian Banks during the period 2014 and 2019. The banks have been selected based upon their size in terms of total assets. The profitability elements, such as Earnings per Share (EPS), Return on Assets (ROA), and Return on Equity (ROE) are the dependent variables; Total Debt Ratio (TDR), Tier 1 Capital Ratio (Tier 1 CAP), and Debt to Equity Ratio (DE) are the independent variables, and firm size is the control variable. The study estimates a pooled regression analysis to analyze the effect of these variables. The results of the study show that there is a positive relationship between the different profitability variables and Debt to Equity Ratio. The Total Debt Ratio is having positive association with ROA and ROE, and has an insignificant negative relationship with the EPS, and the Tier 1 capital ratio is having positive association with ROA and ROE, and has an insignificant relationship with the EPS.